Three-dimensional topographic relief of the oceanic crust may control the occurrence of shallow very-low-frequency earthquakes in the Nankai Trough off Kumano - Kazuya Shiraishi; Yasuhiro Yamada; Masaru Nakano; Masataka Kinoshita; Gaku Kimura (Earth, Planets and Space, 2020)
Abstract To explore a local relationship between geological structures and the occurrence of very-low-frequency earthquakes (VLFEs), a particular class of slow earthquakes with characteristic periods of 10–100 s, we investigated three-dimensional (3D) structural features using reprocessed 3D seismic data from the Nankai Trough off Kumano, southwestern Japan. In this region, VLFEs have been observed along the subducting Philippine Sea Plate. Although the detailed source distribution of VLFEs was estimated by means of recent land-based and offshore seismic networks, the relation with geological features is not well understood. First, we reprocessed the 3D seismic data with advanced techniques and reinterpreted the fault distribution in the sediment layer of the accretionary prism and tracked two key horizons: a décollement and the oceanic crust surface. In the accretionary prism sediments, multiple continuous reflectors of basal detachments in the underthrust sequence and conjugate faults cutting the shallow imbricated thrust sequence were identified. In contrast to the gentle variation in the décollement surface, the topographic relief of the oceanic crust was prominent, with ridges and surface displacement due to faults in the oceanic crust. Then, we compared the structural features with the VLFE source locations. Most VLFEs were located deep in the underthrust sediments where the sediments may consist of underconsolidated muds. Furthermore, a high spatial correlation was observed between the VLFE distribution and the oceanic crust topographic relief. The maximum stress direction, which was inferred from the conjugate faults in the imbricated thrust zone, was consistent with the spatial relation between the VLFE localization and the oceanic crust central ridge. Oceanic crust ridges may cause strain accumulation in the underthrust sediments on the landward sides of the ridges, and low-angle slow thrust movements might be caused using weak slip planes in the underthrust muddy sediments. That is, the topographic relief of the oceanic crust may control the occurrence of shallow VLFEs in the Nankai Trough.